Housing valuation of different towns using the hedonic model: A case of Faisalabad city, Pakistan. (December 2015) - Shabana,; Ali, Ghaffar; Bashir, Muhammad Khalid; Ali, Hassan
Abstract: The present study was planned to determine housing valuation in Faisalabad city using hedonic approach and to estimate the association of determinants which may influence the value of houses in the selected urban communities of the city. To this end, 10 residential towns of Faisalabad city were selected to record data on a pre-designed questionnaire from randomly selected respondents (n = 20) from each town. Co-efficients of regression for the given data variables were calculated and subjected to the hedonic model. It was found that irrespective of the residential towns, people are willing to pay more for new houses, more covered area, lenter, kitchen, garage, lawn and drinking water supply (R 2 > 0.9; P < 0.05). Literacy rate, business and monthly income of the neighbours positively influenced the willingness of consumers to pay more for housing in the study towns (R 2 > 0.9; P < 0.05). Parks, sewerage system and solid waste management system are positively associated with the housing price (R 2 > 0.9; P < 0.05). However, preference of the industrial zone in Faisalabad city is not statistically associated with the price of houses (R 2 < 0.5; P > 0.05). The results of the study provided the first report on the hedonic modeling of housing system in the indigenous situation of Faisalabad which suggested different alternatives to the policy makers and house buyers of different socio-economic values in Faisalabad city. It is suggested that the characteristics positively associated with the housing valuation are required on urgent basis to the residents of Faisalabad. Highlights: Hedonic Model is used to estimate the houses' prices in Faisalabad city. The first baseline data of the hedonic approach implemented in the complicated property market of Pakistan. Environmental variables were found associated with the housing valuation in most of the studied towns. Different attributes of houses positively or negatively affect the value of houses.